Urbanizacja wsi jako przejaw historycznego procesu rozwoju rynku - Czyżewski, Andrzej (Wydział Prawa i Administracji UAM, 1977)
In our treatise we attempted to present role of the market factor in the development of broadly meant country urbanization processes. From the historical point of view the development of market processes consists in a change of closed and self — sufficient production — consumption structure into another structure having advanced marked motivation of production decisions and based upon an analysis in terms of price, output and profit. Lack of above terms or their imperfect performance in the country of feudal and capitalistic Poland did not provide an effective alternative of work beyond agriculture. The situation has changed after the second world war. Dynamic development of non — agricultural activities has contributed to above change, which has definitely extended the labour market, thus causing a growth of consumptional demand for agricultural products and resulting in an (increase of market-bound process of meeting needs in the country. While pointing at the market mechanism as the factor which contributed to the process of changes lin rural areas one must emphasize however that in socialistic economy said process is not model — like pure. One must accept the fact however that economic relations of realization in the country of Poland assume the market form, while being part of planned or state controlled system. In further considerations mediums and symptoms of country urbanization were discussed, showing an effect of the following factors, namely migration of people, transfer of commodities and infiltration of technical progress. Said factors induce a change in living conditions in the country and determine spatial transformations, infrastructural modifications, rising standard of flat furnishings, etc. All these phenomena are admittedly a function of expenditures, which are largely effected by revenues created and realized through the market. Above revenues influence an extent and range of country urbanization, in which economic factors are ranking first.
Country Urbanization as Symptom of Historical Market Development Process